Spatial variability analysis of reference evapotranspiration in Iran utilizing fine resolution gridded datasets - Raziei, Tayeb (2015)
Monthly averages of maximum and minimum temperature, mean relative humidity, sunshine duration and wind speed at 2 m height, relative to 148 Iranian weather stations and period 1991–2005 were utilized for interpolation and gridding the variables to 1◦ in latitude and longitude. The Ordinary kriging method was used coupled with a spherical isotropic variogram. Monthly precipitation of the APHRODITE dataset was regridded to the same mesh grid for computing the aridity index jointly with the gridded variables. The required elevation for estimation of ETo at each grid node was extracted from the digital elevation map of Iran. The adequacy of gridded variables was proved through a set of statistical indicators applied to the cross-validated interpolation errors. The Penman–Monteith (PM-ETo) reference evapotranspiration (ETo) was estimated using the gridded variables and statistically compared with those of observational datasets relative to some stations covering all climatic regions of Iran. Results indicated that the PM-ETo computed using gridded variables well fitted the PM-ETo computed using observed full weather variables at those selected stations. ETo was also estimated by the Hargreaves–Samani (HS) and FAO-PM temperature (PMT) methods using gridded variables of minimum and maximum temperature (Tmin and Tmax). To estimate ETo with HS and PMT methods, appropriate kRs, an empirical radiation adjustment coefficient, were considered for each station, whereas Tmin was adjusted for estimation of the dew point temperature (Tdew) used for PMT computation. It was found that the appropriate kRs for both HS and PMT methods are identical all over the country and they are smaller in dry-sub-humid to humid areas and higher in semiarid to hyper-arid climates. The result suggested that the HS and PMT methods appropriately predict ETo all over Iran if the appropriate kRs are utilized. The spatial patterns of ETo computed with HS and PMT methods found to be identical and resemble to that of PM-ETo, all showing a gradual increasing from north to south, with the lowest ETo values observed over northern humid and sub-humid climates of Iran and larger ETo for arid and hyper-arid climates in the southern and eastern country. Results indicated that the HS and PMT methods are appropriate alternatives for estimation of ETo for all climatic regions of Iran, either when using observation or gridded data